The Morpho-syntactic Alternations of Old English Verbs of Inaction - Ojanguren López, Ana Elvira (International Journal of English Studies, 2022)
The aim of this article is to describe the morpho-syntactic alternations of Old English verbs of inaction. The method includes the analysis of the syntactic constructions in which verbs of inaction are found and of the alternations themselves, which are described as to argumenthood, morphological case, prepositional government and structural complexity. Two types of alternation are identified on the basis of the affected argument. The dative alternation and the reflexive alternation involve both the first and the second argument, whereas the nominalisation alternation and the genitive alternation are restricted to the second argument. The main conclusions are that the alternations found with inaction verbs consist of two alternants that show different degrees of semantic and syntactic integration, and that the consistent distribution of alternations justifies the classification of the set of classes of inaction proposed in this article.